From Neutrality to Alliance: A Defensive Realism and Normative Analysis of Sweden's NATO Accession - Natanael Estrada Simanjuntak (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2026)
This article examines the radical transformation of Swedish security policy, culminating in its 2024 accession to NATO after two centuries of military neutrality. It seeks to answer how and why this profound shift occurred, integrating two key theoretical frameworks: Defensive Realism and the Norms Life Cycle. The article argues that this transformation is best understood as a two-level process. First, Defensive Realism explains the 'why,' positioning Sweden’s decision as a rational, defensive, and security-maximizing response to a severe and worsening security dilemma. This dilemma was precipitated by Russia's escalating material threats, particularly its 2014 annexation of Crimea and the 2022 full-scale invasion of Ukraine, which rendered Sweden's self-help policy of armed neutrality insufficient for national survival. Second, the Norms Life Cycle theory provides the 'how,' detailing the process by which this external material threat acted as a powerful catalyst. This shock created a 'tipping point,' triggering a rapid 'norm cascade' that broke the institutional and identity-based lock-in of the neutrality norm, allowing a new norm of collective defense to be rapidly socialized, accepted, and internalized by elites and the public.